Apocryphal writings relating to the Old and New Testaments and the Jewish and Christian position on it - Al-Shabrami, Maha AbdelRahman Rahma (Journal of Islamic Sciences, 2023)
This research aims to clarify the ambiguity about Apocryphal writings, the difference about the legality of some, resulting by reference to flounder fathers about the legality of the Biblica canon, and indiscipline of acceptance criteria of the bible and the gospels, and the studying of the time gap between acceptance and refusal of the apocryphal writings. The study used the analytical approach and the critical approach, and the most important results of the research are: 1- The difference and turbulence of the church position regarding the Old Testament apocrypha still exists to this day. 2- The absence of fixed criteria upon which the Jewish and Christian churches rely to determine the legal writings. The criteria that they mentioned in their books cannot be relied upon, as some of them apply to what is legal and sacred, and some apply to what is illegal. 3- The distortion by addition, through the difference of the Septuagint version from the Hebrew original by adding the books of the Jewish Apocrypha.